1998
DOI: 10.1038/sj.onc.1201796
|View full text |Cite
|
Sign up to set email alerts
|

The BPV-4 co-carcinogen quercetin induces cell cycle arrest and up-regulates transcription from the LCR of BPV-4

Abstract: Bracken fern is the environmental co-carcinogen of BPV-4 in the induction of neoplasias of the upper alimentary canal of cattle. The¯avonoid quercetin is one of the most potent and best characterised mutagens present in the fern. We have shown that transfection with BPV-4 DNA and exposure to a single dose of quercetin leads to tumorigenic transformation of primary bovine cells. We now show that quercetin induces cell cycle arrest and up-regulates transcription from the BPV-4 long control region (LCR). This up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Previously it has been suggested that there is an initiator in the BPV-4 promoter just downstream from the TATA box (32). The addition of this putative initiator to the BPV-4 promoter sequence used here resulted in a slight elevation in response to E2 but played no role in the epithelial-specific response to E2.…”
Section: Discussionmentioning
confidence: 73%
“…Previously it has been suggested that there is an initiator in the BPV-4 promoter just downstream from the TATA box (32). The addition of this putative initiator to the BPV-4 promoter sequence used here resulted in a slight elevation in response to E2 but played no role in the epithelial-specific response to E2.…”
Section: Discussionmentioning
confidence: 73%
“…In this system, quercetin confers anchorage-independence, immortalisation and tumourigenicity, so that the only BPV-4 oncogene required for full transformation is E7 [26]. A cis-acting element responding to quercetin has been mapped in the BPV-4 LCR [42] whose activation leads to E7 oncoprotein expression. This likely induces the transformed cells to bypass the quercetin-induced G1 cell cycle arrest and to proliferate [13].…”
Section: Bpv-4 and Gastrointestinal Tumoursmentioning
confidence: 99%
“…Quercetin is mutagenic in both prokaryotic and eukaryotic cells, and is clastogenic, leading to single-strand DNA breaks [33,106] and chromosomal rearrangements [77]. It promotes the full in vitro transformation of primary bovine cells infected with BPV-4 DNA [26,99] and upregulates viral DNA transcription via a cis-acting element in the viral transcriptional promoter [42]. Moreover, bracken eating cattle with BEH and/or suffering from bladder cancer develop chromosomal abnormalities [67,80,88,101,129] due to a clastogenic activity of compounds from fern.…”
Section: Bracken Fern As a Cofactor For Carcinogenesismentioning
confidence: 99%
“…O sinergismo entre a infecção por BPV-4 e a exposição à quercetina, um flavonóide carcinogênico presente na samambaia (Pamucku et al 1980, Musonda & Chipman 1999) na transformação celular foi estabelecido em estudos in vitro (Pennie & Campo 1992, Cairney & Campo 1995, Connolly et al 1998, Beniston et al 1999, 2001). Entretanto, a comprovação deste sinergismo in vivo não foi completa, pois bovinos infectados pelo BPV-4 e tratados somente com quercetina não apresentaram malignização dos papilomas (Campo et al 1994).…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified